Growth, biofiltration and photosynthetic performance of Ulva spp. cultivated in fishpond effluents: An outdoor study - Massocato, Thaís Fávero; Robles-Carnero, Víctor; Moreira, Bruna Rodrigues; Castro-Varela, Pablo; Pinheiro-Silva, Lorena; Oliveira, Willian da Silva; Vega, Julia; Avilés, Antonio; Bonomi-Barufi, José; Rörig, Leonardo Rubi; Figueroa, Félix L. (Frontiers in Marine Science, 2022)
Anthropogenic impacts on water resources, especially by ​​nutrient discharge, is a worldwide problem in marine coastal areas. In this context, seaweed cultivation in aquaculture wastewater can be considered as an alternative for effluent mitigation, where the biomass becomes a source of valuable compounds. The current study examined the potential use of the seaweeds Ulva pseudorotundata and Ulva rigida to remove nutrients to treat effluents from the culture of Chelon labrosus. Two experiments were conducted under pilot-scale conditions to evaluate the nutrient uptake, photosynthetic activity, and biomass production of the seaweed species cultivated under 50 and 100% effluent concentrations. Photosynthetic parameters were determined by in vivo chlorophyll a fluorescence associated to photosystem II 3 times a day to estimate photosynthetic performance and seaweed physiology throughout the experiment: optimal quantum yield (Fv/Fm), in situ and ex situ electron transport rate (ETR), photosynthetic efficiency (αETR), saturation irradiance (Ek), and the maximum non-photochemical quenching (NPQmax). To evaluate seaweed metabolism and biomass compounds, elemental and biochemical composition were analyzed in the beginning and end of each experiment. Results regarding the nutrient source showed that both species removed more than 65% of ammonium after 3 hours of experimentation. At the end of the experiments, up to 94.8% of the initial ammonium was sequestered from the effluent. Additionally, after 5 days of cultivation under 50% fish effluent both Ulva species were able to remove more than 85% of the nitrate. Although a decrease in uptake efficiency was observed in cultures with 100% fish effluent, at the end of the experiment more than 440 µmol L-1 of nitrate was removed, considering all treatment conditions. The biomass values showed that growth rates of seaweed cultivated in 100% effluent were higher than those obtained in 50% effluent. Moreover, when cultivated in the 100% effluent concentration, a significant increment in protein content was detected in both Ulva species. Our results contribute to the understanding of biofiltration and photosynthetic performance of two different Ulva species in order to improve growth optimization, enhancement of biofiltration capacity and also to boost management practices of seaweed cultivation in aquaculture effluent treatment systems.